Insight into the stability and correlated transport of kaolinite colloid: Effect of pH, electrolytes and humic substances. (November 2020) - Sun, Yalou; Pan, Duoqiang; Wei, Xiaoyan; Xian, Dongfan; Wang, Peng; Hou, Junjun; Xu, Zhen; Liu, Chunli; Wu, Wangsuo
Abstract: Environmental colloids play crucial roles in the transport of environmental pollutants in porous media by acting as pollutant carriers. In this work, the dispersion stability and correlated transport of kaolinite colloid were investigated as a function of solution pH, solution ionic strength, and concentration of humic acid (HA), the roles of kaolinite colloid in driving Eu(III) transport were discussed. The results showed that the dispersion of kaolinite colloid was favorable at alkaline and extremely acidic pH values, the trend of aggregation with varying pH was critically reversed at pH ∼3.2 due to the transformation of surface electrical properties. Cations with higher valence and mineral affinity showed a more significant contribution in inducing colloid aggregation, which was generally in accordance with the Schulze-Hardy rule and Hofmeister series. HA greatly increased the colloid stability by altering the surface electrostatic potential and steric effect. The Derjguin-Landau-Verwey-Overbeek (DLVO) model suggested that the electrostatic force between colloidal particles controlled the aggregation and destabilizing trend of colloid, and the theoretically calculated critical coagulation concentration was consistent with that determined from kinetic aggregation experiments. The roles of kaolinite colloid in driving Eu(III) transport varied under different conditions, and the transport behavior was highly correlated with the dispersion stability trend of colloid. These results can provide an enhanced understanding of the environmental fate of kaolinite colloid as well as commensal pollutants. Graphical abstract: Image 1 Highlights: Kaolinite colloid is dispersion favorable under high pH and extreme low pH. Ions with high valence and mineral affinity are significant in inducing aggregation. Humic acid greatly increases the dispersion stability of kaolinite colloid. Transport of colloid and Eu(III) is related with the dispersion stability of colloid.